2011
DOI: 10.1007/s00394-011-0239-7
|View full text |Cite
|
Sign up to set email alerts
|

Excessive iodine intake in schoolchildren

Abstract: The results show that the iodine nutritional status of the schoolchildren studied is characterized by a high urinary iodine excretion, which might reveal an increase in iodine consumption by this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
1
13
0
7
Order By: Relevance
“…Nutritional status of iodine has been evaluated using urinary iodine quantification in addition to other indirect methods, such as hormonal dosage tests and ultrasound of the thyroid (1,5,8,11). Urinary iodine (UI) represents a good indicator of the recent ingestion of iodine, as 90% of ingested iodine is expelled through the urine (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional status of iodine has been evaluated using urinary iodine quantification in addition to other indirect methods, such as hormonal dosage tests and ultrasound of the thyroid (1,5,8,11). Urinary iodine (UI) represents a good indicator of the recent ingestion of iodine, as 90% of ingested iodine is expelled through the urine (19).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the recommended maximum fortification of salt with iodine has varied between 60mg and 100mg of iodine/kg of salt, according to evidence regarding excesses or deficiencies of iodine (5-7). Although the current limit is 60mg/kg of salt (4), in certain regions of the country, excessive levels of urinary iodine have been reported in some groups of people, such as children (8), adults who live in metropolitan areas and people who have heart conditions (1,5). However, these findings do not represent all population groups and should not be generally extrapolated to the country's population.…”
Section: Introductionmentioning
confidence: 94%
“…Nuestros hallazgos sugieren que la mediana de yoduria disminuye conforme se incrementa la edad de los escolares, esto difiere de lo reportado por Carvalho et al, que refieren que la mediana de yoduria aumenta con la edad; una posible explicación seria que, en Brasil, la concentración de yodo en sal es 20 a 60 mg/kg (17) mientras que, en Perú, la concentración de yodo en sal es 30 a 40 mg/kg. La mediana de yoduria en Lima Metropolitana presentó niveles mayores a los recomendados por la OMS (311,5ug/L) mientras que la menor concentración de yoduria se presentó en la selva (216,9 ug/L).…”
Section: Discussionunclassified
“…While the Southeast region has been recognized as an iodine sufficient area, differences were also detected between states from the same region (Minas Gerais vs. São Paulo). In São Paulo, there is a rising concern regarding the excessive iodine exposure and predisposition to thyroid autoimmune diseases (Table 2) (29,33,36,40). In contrary, in the state of Minas Gerais, few studies have reported increased IDD prevalence, especially in children and adolescents from low-income populations (Table 2) (37,38).…”
Section: Discussionmentioning
confidence: 99%